WHAT’S ON YOUR MIND? MEASURING SELF-PROMOTIONAL AND ANTI-SOCIAL BEHAVIORS ON FACEBOOK AMONG TERTIARY STUDENTS - Dave E. Marcial (Інформаційні технології і засоби навчання, 2015)
The social media revolutionized the power of collaboration and networking. If overused and misused, it provides negative impacts among users. This paper presents the prevalence of self-promotional behaviors on Facebook among students in a university in the Philippines. A total of 106 college students were randomly selected as respondents of the study. An adapted survey questionnaire was used during analysis. The results show that the respondents promote their selves on Facebook every semester. Specifically, the result shows that the respondents update their status, post photographs of their selves and change profile pictures once a month. On the other hand, the respondents update their profile information, tag pictures of their selves and upload “selfie” pictures every semester. It is concluded that the students sometimes possess behaviors that tend to be tied to narcissism on Facebook.